2017
DOI: 10.1002/pmh.1393
|View full text |Cite
|
Sign up to set email alerts
|

High novelty seeking as a predictor of antisocial behaviour in early adulthood

Abstract: Alcohol and substance use disorders mediate the association between NS and antisocial behaviours in early adulthood. NS may be a useful endophenotype for investigating the causation of externalizing behaviours. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Human development is a complex phenomenon involving the joint influence of socioecological conditions and individual dispositional characteristics. As such, one's temperament is defined as an individual characteristic which comprises a habitual mode of emotional response to stimulus [17,26]. Foulds et al (2017) [26] stated that the temperament has been traditionally viewed as an emotional and behavioural characteristic of feelings and presumed to be more biologically rooted by maturation and heredity.…”
Section: Difficult Temperamentmentioning
confidence: 99%
See 2 more Smart Citations
“…Human development is a complex phenomenon involving the joint influence of socioecological conditions and individual dispositional characteristics. As such, one's temperament is defined as an individual characteristic which comprises a habitual mode of emotional response to stimulus [17,26]. Foulds et al (2017) [26] stated that the temperament has been traditionally viewed as an emotional and behavioural characteristic of feelings and presumed to be more biologically rooted by maturation and heredity.…”
Section: Difficult Temperamentmentioning
confidence: 99%
“…As such, one's temperament is defined as an individual characteristic which comprises a habitual mode of emotional response to stimulus [17,26]. Foulds et al (2017) [26] stated that the temperament has been traditionally viewed as an emotional and behavioural characteristic of feelings and presumed to be more biologically rooted by maturation and heredity. Prior research has found that children who throw tantrums will usually react negatively towards people around them, have a low level of bonding with their parents (poor parent-children interaction), and develop various forms of psychopathological problems including antisocial behaviour [29].…”
Section: Difficult Temperamentmentioning
confidence: 99%
See 1 more Smart Citation
“…Different biological factors have an implication in developing antisocial behavior, such as brain damage during pregnancy, brain hypoxia in the womb or birth, or neuropsychological dysfunction and psychosocial influences [ 6 ]. A number of studies also showed that environmental factors have a major role in the creation of antisocial behavior, especially during childhood [ 7 ]. Examples of such factors include; the person exposed to domestic violence and abused in his home, his parents being drug users, was abused during his childhood either sexually, physically, or emotionally or an unstable home environment [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies also showed that environmental factors have a major role in the creation of antisocial behavior, especially during childhood [ 7 ]. Examples of such factors include; the person exposed to domestic violence and abused in his home, his parents being drug users, was abused during his childhood either sexually, physically, or emotionally or an unstable home environment [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%